Growth and endocrinopathies among children with β-Thalassemia major treated at Dubai Thalassemia centre - Rabah Almahmoud; Amal Hussein; Fatheya Al Khaja; Ahmed Farrag Soliman; Hany Dewedar; Zainab Al Shareef; Sarah Mathai (BMC, 2024)
Abstract Background β-Thalassemia major (BTM) is one of the most common hereditary anemias worldwide. Patients suffer from iron overload that results from repeated blood transfusion This in turn leads to multiple organ damage and endocrinopathies. This study aims to assess the prevalence of growth retardation, hypothyroidism, and diabetes mellitus in children and adolescents with BTM treated at Dubai Thalassemia Centre. Methods A total of 105 children and adolescents were included in this retrospective observational study. Results 39 children and 66 adolescents' data were analyzed. Females composed 51.3% (n = 20) of children and 53.0% (n = 35) of adolescents. Pretransfusion hemoglobin below 9 gm/dl was observed in 10.8% (n = 4) and 10.6% (n = 7) in children and adolescents, respectively. The mean age of menarche was 13.5 years. Among all study participants, 22.6% (n = 14) had normal height velocity whereas 37.1% (n = 23) had reduced height velocity in one year and 40.3% (n = 25) had reduced height velocity in two consecutive years. The proportion of children and adolescents showing reduced height velocity was significantly higher in females compared to the males (90.6% versus 63.3%, respectively, Chi-square = 6.597, p-value = 0.010). Although none of the study participants had diabetes mellitus, 26.1% (n = 12/46) had pre-diabetes. Elevated TSH was observed in 14.7% (n = 5) children and 8.1% (n = 5) adolescents while low FT4 was reported in one child and one adolescent. Conclusion Of all endocrinopathies seen among children and adolescents with BTM, growth delay remains the main concern for this group of patients. Effective treatment is key to further reducing endocrinopathies. Although the sample size is limited, we postulate that the low percentage of endocrinopathies among children with BTM treated at Dubai thalassemia center and the low level of pretransfusion anemia reflect the effective transfusion and chelation at the center.